2021
DOI: 10.1107/s2056989021002383
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of 4-(4-chlorophenyl)-5-methyl-3-{4-[(2-methylphenyl)methoxy]phenyl}-1,2-oxazole

Abstract: In the title compound, C24H20ClNO2, the mean planes of 4-chlorophenyl, 2-methylphenyl and phenylene rings make dihedral angles of 62.8 (2), 65.1 (3) and 15.1 (2)°, respectively, with the 5-methyl-1,2-oxazole ring. In the crystal, molecules are linked by intermolecular C—H...N, C—H...Cl, C—H...π contacts and π–π stacking interactions between the phenylene groups. Hirshfeld surface analysis indicates that the most important contributions to the crystal packing are from H...H (48.7%), H...C/C...H (22.2%), Cl...H/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Benzyl analogues differently substituted at 3-(19-23) or 4position (24−29) were not chased further as they demonstrated a significant loss of inhibitory activity (IC 50 values of 12 to >20 μM) for both cell lines except for 20 with 3-methoxy, which showed comparable activity to 11 for the Huh7 cell line (IC 50 = 1.3 vs 3.6 μM). Compounds with dimethyl substitution pattern, i.e., 2,3-diMe (30) or 2,4-diMe (31), suggested that additional methyl group other than 2-methyl was not well tolerated on the benzyl moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzyl analogues differently substituted at 3-(19-23) or 4position (24−29) were not chased further as they demonstrated a significant loss of inhibitory activity (IC 50 values of 12 to >20 μM) for both cell lines except for 20 with 3-methoxy, which showed comparable activity to 11 for the Huh7 cell line (IC 50 = 1.3 vs 3.6 μM). Compounds with dimethyl substitution pattern, i.e., 2,3-diMe (30) or 2,4-diMe (31), suggested that additional methyl group other than 2-methyl was not well tolerated on the benzyl moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to the SAR results, compound 11 with 3,4diarylisoxazole and compound 85 with 1,5-diarylpyrazole frameworks were selected for further analysis, and unambiguous structural elucidation of 11 and 85 using the single-crystal X-ray diffraction method was accomplished showing the accurate rearrangement of aromatic rings and atoms in 3Dshape (Figure S1). 29,30 Next, judged by the cellular activity of 11 and 85, both compounds in addition to Huh7, Mahlavu, and MCF7 cell lines were further screened against a panel of the hepatocellular carcinoma (HepG2, SNU475, Hep3B, FOCUS, Hep40, and PLC-PRF-5) and breast cancer (MDA-MB-231, MDA-MB-468, SKBR3, and ZR-75) cell lines along with the nontumorigenic immortalized breast epithelial cells MCF10A (Table 5). The results demonstrated that both compounds are endowed with potent antiproliferative activity against all cancer cells with IC 50 values in the range of 1.3−9.5 μM for 11 and 0.77−7.8 μM for 85 for hepatocellular carcinoma and breast cancer cell lines, while found less toxic to the MCF10A immortalized normal breast epithelial cells (Table 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the synthesis of compound ( 9 ); the cycloaddition reaction of arylnitriloxide ( 8 ) and 4‐chlorophenylacetone ( 7 ) was carried out as in literatures. [ 38,47,48 ]…”
Section: Methodsmentioning
confidence: 99%
“…For the synthesis of compound (9); the cycloaddition reaction of arylnitriloxide (8) and 4-chlorophenylacetone (7) was carried out as in literatures. [38,47,48] 2.3.1 | Synthesis of 4-(4-[4-chlorophenyl]-5-methylisoxazol-3-yl)phenol (10) The synthesis of compound 10 was prepared as in the literature with little modification. [49] To a solution of compound 9 (1.0 g, 2.66 mmol) and Pd/C (10%, 0.18 g) in ethyl acetate (100 ml) was stirred at room temperature under H 2 atmosphere.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation